2014
DOI: 10.1128/jvi.00289-14
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Human Enterovirus 71 High-Replication-Fidelity Variants in AG129 Mice

Abstract: In a screen for ribavirin resistance, a novel high-fidelity variant of human enterovirus 71 (EV71) with the single amino acid change L123F in its RNA-dependent RNA polymerase (RdRp or 3D) was identified. Based on the crystal structure of EV71 RdRp, L123 locates at the entrance of the RNA template binding channel, which might form a fidelity checkpoint. EV71 RdRp-L123F variants generated less progeny in a guanidine resistance assay and virus populations with lower mutation frequencies in cell culture passage du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 48 publications
3
79
0
Order By: Relevance
“…Cooperation of variants within quasispecies has been described in poliovirus and enterovirus 71 pathogenesis. 18,19 Several possible mechanisms could contribute to the small plaque phenotype of the virus. Previous study on West Nile virus showed amino acid substitutions in NS4B protein, a small poorly defined protein, associated with small plaque phenotype and the resulting virus induced less innate and adaptive immune responses in mice when compare to wild type virus.…”
Section: Virulence Of Wild Type and Small Plaque Variant Of Chikvmentioning
confidence: 99%
“…Cooperation of variants within quasispecies has been described in poliovirus and enterovirus 71 pathogenesis. 18,19 Several possible mechanisms could contribute to the small plaque phenotype of the virus. Previous study on West Nile virus showed amino acid substitutions in NS4B protein, a small poorly defined protein, associated with small plaque phenotype and the resulting virus induced less innate and adaptive immune responses in mice when compare to wild type virus.…”
Section: Virulence Of Wild Type and Small Plaque Variant Of Chikvmentioning
confidence: 99%
“…151 However, the possibility to engineer attenuated high-fidelity-variants of EV-A71 with low pathogenicity could be a promising approach for future live vaccines. 152 In a comparative study of prototyptic EV-A71 vaccines produced by different technologies, formalin-inactivated EV-A71 virions adjuvanted in alum were found to be very immunogenic, to elicit strong cross-neutralization titers against different EV-A71 genotypes and subgenotypes in mice and non-human primates and to be the most potent and promising immunogens.…”
Section: Ev-a71 Vaccines: the First Step Toward Multivalent Hfmd Vaccmentioning
confidence: 99%
“…Ribavirin has been used to select high-fidelity variants of EV71 (21,43), footand-mouth disease virus (FMDV) (44,45), and chikungunya virus (22), suggesting that these viruses occupy the lower end of the fidelity spectrum. One might expect that the need to retain crossspecies infectivity in zoonotic arboviruses necessitates higher-fidelity polymerases, as implied by yellow fever virus fidelity data (46), although data from dengue virus polymerase suggest that it has a fidelity comparable to those of PV and FMDV RdRPs based on single nucleotide incorporation assays (47).…”
Section: Fig 8 Comparison Of Coxsackievirus and Poliovirus Polymerasementioning
confidence: 99%
“…Maintaining the proper genome heterogeneity is essential for virus fitness, as it allows rapid adaptation to different host environments, and viral pathogenesis can be attenuated by increasing or decreasing polymerase fidelity (16). This has been shown for poliovirus (PV), coxsackievirus B3 (CV), and enterovirus 71 (EV71) in mouse studies (17)(18)(19)(20)(21) and for chikungunya virus, where fidelity variants lose fitness in both vertebrate and invertebrate hosts (22,23).…”
mentioning
confidence: 99%